Pelatihan Elektronika Dasar Berorientasi Kewirausahaan bagi Generasi Z Berbasis Laboratorium - Haris, Abdul; Martawijaya, M.A.; Saleh, Muh.; Hasyim, Mutahharah; Mahir, Mahir (LP2M Universitas Muhammadiyah Enrekang, 2024)
This article discusses a basic electronics training program oriented towards entrepreneurship for Generation Z. Generation Z, known as the digital generation, has significant potential to develop technical and entrepreneurial skills relevant to the demands of Industry 4.0. This training is designed to provide fundamental understanding of electronics while equipping participants with the entrepreneurial knowledge and skills necessary to create new business opportunities in the field of technology. Through a practical approach and real projects, participants are expected to design and develop simple electronic products, as well as understand basic business concepts such as planning, marketing, and financial management. The results of the training show a significant improvement in the participants' technical and entrepreneurial skills, as well as an increased interest in further exploring business potential in the field of electronics. This article also evaluates the challenges and opportunities faced in the implementation of this training program, and provides recommendations for the development of similar training programs in the future